Analysis of a hybrid wireless power harvester for low power applications - Awal, M. R. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper proposes a hybrid approach to harvest power through piezo-electromagnetic transduction. This technique is composed of a piezo and electromagnetic transducer on a common platform. The novel duality of piezoelectricity and piezomagnetism in some dielectric materials are focused here to combine the process. The feasible power from the device is calculated through individual and combined boundaries. It is evident from the investigation that, certainly the combination increases the robustness of the device for low power load applications. However, the individual power output remains the same.